PEMBELAJARAN SOSIAL MAHASISWA UNIVERSITAS ISLAM BUNGA BANGSA CIREBON DALAM MENGAKSES KONTEN DAKWAH DI MEDIA SOSIAL INSTAGRAM PADA AKUN @shiftmedia.id - Rifqi Fauzi; Saeful Malik; Asep Ahmad Mausul (Program Studi Komunikasi dan Penyiaran Islam, Fakultas Dakwah dan Komunikasi, Universitas Islam Bunga Bangsa Cirebon, 2023)
The phenomenon of da'wah on Instagram raises questions about social learning (social learning) Instagram as a medium of da'wah and can be seen from the many findings of the hijrah movement campaign through Instagram. This is not a few young people who study religion through social media, one of which is through Instagram. However, the rise of #hijrah on Instagram is not enough to indicate the success of da'wah. So the phenomenon of migration on Instagram does not guarantee a change in a person. Therefore, da'wah can be said to be effective if it is able to educate, motivate or change the behavior of the target da'wah for the better (hijrah) religiously. This study aims to determine audience attention, audience retention, audience motor reproduction, and audience motivation in accessing da'wah content on social media Instagram on the account @shiftmedia.id. This research is a type of qualitative research with a case study approach. The informants in this study were students IAI Bunga Bangsa Cirebon who joined or became followers on the Instagram account @shiftmedia.id as many as 8 people. Data collection techniques in this study were carried out through observation, interviews, and documentation. Furthermore, checking the validity of research data using source triangulation techniques and method triangulation to test the validity of data related to the research problem studied by the researcher. The results of this study indicate that the delivery of da'wah through video content via Instagram on the account @shiftmedia.id can be said to be effective. This can be seen from the da'wah video on the Instagram account @shiftmedia.id that is able to provide religious understanding and shape the motivation and behavior of hijrah on informants. However, the motivation and behavior of hijrah are also influenced by the intensity and attention of the informants in accessing the da'wah videos on the account. A person with a higher level of attention, retention and motor reproduction will produce greater hijrah motivation and more progressive hijrah behavior through social learning.